(untitled) (Experimental biology, 2015)
It was established that 3 months after the injection of allogeneic cells to rats with different individual typological peculiarities of behavior the changes in blood cell content of rats were more pronounced then compared with those obtained after 6 and 9 months. It was shown a slight decline in all blood parameters after 3 months, less profound - after 6 months and restoration - 9 months after the introduction of MNCs.